2023
DOI: 10.32468/be.1236
|View full text |Cite
|
Sign up to set email alerts
|

Reparations as Development? Evidence from Victims of the Colombian Armed Conflict

Abstract: Our study is the first to investigate the effects of reparations for victims of gross human rights violations. In Colombia, victims of forced displacement, homicide, and other atrocities during the conflict received a lump-sum payment equal to three times their annual household income. Using novel linked administrative microdata and event studies, we show that reparations help victims rebuild their lives and significantly improve their well-being and that of their children. Specifically, reparations promote in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The SSO assignment has implications for both the professionals who are selected randomly and the communities that get assigned doctors with different qualities. The latter are the focus of the present paper; the implications for the professionals are studied in Guarin, Posso, Saravia, and Tamayo (2023). In this paper, we use the exogenous rule of assignment to compare the birth outcomes of patients in LHCs that were assigned professionals with different medical skills but are otherwise comparable.…”
Section: The Experimental Setting: Sso Programmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSO assignment has implications for both the professionals who are selected randomly and the communities that get assigned doctors with different qualities. The latter are the focus of the present paper; the implications for the professionals are studied in Guarin, Posso, Saravia, and Tamayo (2023). In this paper, we use the exogenous rule of assignment to compare the birth outcomes of patients in LHCs that were assigned professionals with different medical skills but are otherwise comparable.…”
Section: The Experimental Setting: Sso Programmentioning
confidence: 99%
“…This high heterogeneity plays in our favor, because it allows us to compare the outcomes of patients who were randomly exposed to physicians with very different baseline knowledge and skills. 26 Using the scores and demographic characteristics from the SABER PRO, Guarin et al (2023) showed that the SSO lotteries in our sample are well balanced between SSO-assigned physicians and those who were randomly exempt. They use individual regressions correlating physicians' characteristics and lottery status as well as machine learning techniques and a classification permutation test to provide evidence of equality of multivariate distributions between treatment and control groups (Gagnon-Bartsch, Shem-Tov, et al, 2019) and the randomness of the selection into the program in general.…”
mentioning
confidence: 90%